2023
DOI: 10.3389/fmed.2023.1099351
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with positive bacterial culture in salvaged red blood cells during cardiac surgery and postoperative infection incidence: A prospective cohort study

Abstract: BackgroundThis study was designed to explore factors associated with the incidence of positive bacterial culture of salvaged red blood cells (sRBCs) recovered with a Cell Saver instrument during cardiac surgery and the impact of such positive outcomes on postoperative infection-related morbidity.MethodsThe cohort study enrolled 204 patients scheduled for cardiac surgery with intraoperative blood cell salvage and retransfusion from July 2021 to July 2022. These patients were stratified into two groups based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Similarly, Khabori et al [ 62 ], found that the use of Cell Salvage did not decrease the transfusion rate [OR: 0.69; 95 % CI: 0.48–1.00). Continuing in the same line, the results of Zhou et al [ 63 ], indicated that patients who underwent surgery using Cell Salvage underwent more allogeneic transfusions and had a longer stay in the ICU, resulting in higher healthcare costs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, Khabori et al [ 62 ], found that the use of Cell Salvage did not decrease the transfusion rate [OR: 0.69; 95 % CI: 0.48–1.00). Continuing in the same line, the results of Zhou et al [ 63 ], indicated that patients who underwent surgery using Cell Salvage underwent more allogeneic transfusions and had a longer stay in the ICU, resulting in higher healthcare costs.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, the results are inconclusive depending on the aspect evaluated, and controversy exists. While several studies suggest that the use of Cell Salvage substantially reduces allogeneic blood transfusions [ [54] , [55] , [56] , [57] , [58] , [59] , [60] ], other authors argue the opposite [ [61] , [62] , [63] ]. In this regard, according to a study by Stoneham et al [ 61 ], patients operated on using Cell Salvage had to be transfused with other allogeneic components within the first 24 h postoperatively.…”
Section: Discussionmentioning
confidence: 99%